The Influence of Effective Leadership Styles and Appraisal Systems towards Employee Performance - Fauziyah, Qorina Hanni (APPS Publications, 2021)
The objective of this study is to investigate how the application of appraisal systems and effective leadership styles using transformational and transactional theories can significantly affect employee performance in a company or organization. For this study, data on the effective leadership style of employees in Jakarta was collected and analyzed to determine the relationship between their effective leadership style and appraisal system and the employee performance. Results showed that transformational leadership style was positively associated with employee performance; transactional leadership style, on the other hand, produced a different result. In addition, the results showed that appraisal system was positively associated with employee performance. This study extends past research by examining the differential aspects of both transformational and transactional on leadership styles.